Etapa Básica de Música Turrialba: A Historical Reconstruction Based on Its Main Actors - Castillo Calvo, Diego Armando (2026)
In order to commemorate the 35th anniversary of the Basic Music Stage, a qualitative investigation was conducted, stemming from a doctoral thesis authored by the principal investigator. Four key stakeholders intimately involved in the inception and evolution of the project participated in this inquiry. The primary outcome of this study yielded valuable insights into the origins of the Basic Music Stage, thereby underscoring its significance over the course of 35 years within the region.